Between global design and domestic realities: Institutional capacity, policy space, and the implementation of OECD Pillar Two - Wardana, Arief Budi (Educoretax, 2025)
Pillar Two of the OECD/G20 Inclusive Framework is often presented as a technocratic solution to curb profit shifting and harmful tax competition by introducing a global minimum tax. This article argues that Pillar Two cannot be understood solely as a technical instrument, but rather as a worldwide institutional reform with significant distributional, capacity-related, and legitimacy implications. This study adopts a qualitative–narrative approach, drawing on panel interviews with key actors in international tax governance, including academics, national tax authorities, policy advisors from developing countries, and corporate tax executives from multinational enterprises. The analysis is guided by an integrated theoretical framework combining historical institutionalism, global tax governance theory, the international political economy of taxation, policy capacity theory, and the Narrative Policy Framework. The findings show that Pillar Two is perceived as a layered institutional reform implemented within heterogeneous domestic tax systems, resulting in structurally embedded complexity and variation in implementation. Actor narratives—particularly from the Global South—highlight significant uncertainty about net revenue outcomes and concerns about policy space erosion from the neutralisation of tax incentives. Fragmented global engagement and uneven administrative capacities further reinforce ambivalent assessments of Pillar Two's effectiveness.